Comparative Histopathological and Morphometric Analysis of Lung Tissues in Stillborn Cubs of South China Tiger and Amur Tiger - Le Zhang; Jincheng Yang; Fengping He; Yaohua Yuan; Zhaoyang Liu; Guangyao Geng; Kaixiong Lin; Qunxiu Liu; Dan Liu; Tianlong Liu; Yanchun Xu (Biology)
This study aimed to determine whether the fetuses experienced hypoxic distress or intra-partum death due to compromised oxygen supply by quantitatively analyzing the lung structures of deceased captive South China Tiger (Panthera tigris amoyensis, SCT) cubs. Furthermore, it investigated the etiology and mechanisms of asphyxia in the deceased cubs and explored potential factors contributing to the high mortality rate of SCT cubs. The research focused on three deceased SCT cubs, using three deceased neonatal Amur Tigers (P. t. altaica, AT) with no inbreeding background as controls. Histological analysis of the cubs’ lungs was conducted using hematoxylin–eosin (H&E) and special staining techniques. The possible causes of death in SCT cubs were evaluated by comparing pulmonary pathological changes and morphological parameters, including alveolar space (P(ASP)) values, mean alveolar linear intercept (Lm), and mean thickness of alveolar septa (Tas). Our research reveals that hypoxia is one of the most significant factors contributing to the mortality of tiger cubs. Additionally, we hypothesize that inbreeding depression may lead to abnormal lung development (e.g., thickening of lung tissue) in SCT cubs. This study lays the foundation for comprehensive investigations into the mortality of highly inbred SCT cubs.